Kerjasama Pusat Kegiatan Belajar Masyarakat dengan Pemerintah Desa sebagai Upaya Meningkatkan Partisipasi Pendidikan Masyarakat - Widiyantoro, Webri (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze educational strategies and patterns of cooperation between community learning activity centers and village governments, and analyze the constraints and efforts made in the process of increasing community education participation. The study used a qualitative approach with a case study method. The cases were chosen were typical cases that be able to represent similar cases, namely a form of collaboration between the community learning activity center and the village government. The qualitative data analysis used was pattern matchmaking analysis, to answer big questions related to strategies, forms, constraints, and solutions in building cooperation between community learning activity centers and village governments. The obtained results indicated that the strategies used by the community learning activity center in the process of increasing community education participation were in the form of community identification strategies, programs, and partnerships. The pattern of cooperation between the community learning center and the village government was in the form of coaching and mentoring, with the form of cooperation in the form of support for policy regulations, legal protection, budget assistance, mentoring, coaching, and motivation. The obstacles faced by the community learning activity center were weak community commitment and less than optimal program socialization. Efforts to overcome these obstacles were carried out by implementing performance and performance strategies and increasing innovation in disseminating educational programs.